0
$\begingroup$

Is it at all possible to rearrange this equation to make c the subject. My dad and I believe it is possible but I am unable to correctly rearrange for c.

$\endgroup$
0
$\begingroup$

This is done using your basic log rules. The main rule to use is: $$y=log_b(x)=>x=b^y$$

So in your case:

$$(a*b)^c=d$$ $$clog(ab)=log(d)$$ $$c=\frac{log(d)}{log(ab)}$$ $$(c=log_{ab}(d))$$

$\endgroup$
1
  • $\begingroup$ Awesome thank you i'd forgotten that logs could be used this way :) $\endgroup$
    – Bayyls
    Nov 16 '15 at 6:28
0
$\begingroup$

Hint: It is possible, but you'll need a logarithm to do it.

Logarithms are the inverses of exponents. If $\log_x(y)=z$, then $x^z = y$; that's the definition of a logarithm.

Can you find what x, y, and z should be in your equation?

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.